Designing the microstructural constituents of an additively manufactured near β Ti alloy for an enhanced mechanical and corrosion response. (May 2022) - Hariharan, Avinash; Goldberg, Phil; Gustmann, Tobias; Maawad, Emad; Pilz, Stefan; Schell, Frederic; Kunze, Tim; Zwahr, Christoph; Gebert, Annett
Graphical abstract: Abstract: Additive manufacturing of near β-type Ti-13Nb-13Zr alloys using the laser powder bed fusion process (LPBF) opens up new avenues to tailor the microstructure and subsequent macro-scale properties that aids in developing new generation patient-specific, load-bearing orthopedic implants. In this work, we investigate a wide range of LPBF parameter space to optimize the volumetric energy density, surface characteristics and melt track widths to achieve a stable process and part density of greater than 99 %. Further, optimized sample states were achieved via thermal post-processing using standard capability aging, super-transus (900 °C) and sub-transus (660 °C) heat treatment strategies with varying quenching mediums (air, water and ice). The applied heat treatment strategies induce various fractions of α, martensite (α', α'') in combination with the β phase and strongly correlated with the observed enhanced mechanical properties and a relatively low elastic modulus. In summary, our work highlights a practical strategy for optimizing the mechanical and corrosion properties of a LPBF produced near β-type Ti-13Nb-13Zr alloy via careful evaluation of processing and post-processing steps and the interrelation to the corresponding microstructures. Corrosion studies revealed excellent corrosion resistances of the heat-treated LPBF samples comparable to wrought Ti-13Nb-13Zr alloys.